(untitled) (Research, Society and Development, 2021)
Objectives: The impairment of the temporomandibular joint and masticatory muscles has a negative impact on functions of the stomatognathic system, such as swallowing. Thus, an atypical swallowing pattern may contribute to the development of temporomandibular disorder (TMD). The aim of the present study was to evaluate acoustic aspects of swallowing and determine the occurrence of atypical swallowing dynamics. Methods: Sixty-two individuals [16 males (25.8%) and 46 females (74.2%); mean age 39.84 (± 9.40); 47 with TMD and 15 without TMD] were evaluated using an ultrasound detector during the swallowing of three consistencies: liquid, pasty and solid. The acoustic signals were recorded and subsequently analyzed using the DeglutiSom® software. Results: The majority of the sample (81%) with TMD presented atypical swallowing biodynamics, with a significantly greater frequency of food residuals for the three consistencies. The signal suggestive of aspiration was more frequent with the liquid consistency (37% of the group). Conclusion: There is a relation between TMD and an atypical swallowing pattern, which underscores the need for the multidisciplinary evaluation of individuals with this disorder.